Surgical re‐excision vs. observation for dysplastic naevi. (17th September 2018) - Vuong, K.T.; Walker, J.; Powell, H.B.; Thomas, N.E.; Jonas, D.E.; Adamson, A.S.
Summary: Pathologists, doctors who study the causes and effects of diseases, look at samples of skin under the microscope. Unusual moles of the skin, called histologically dysplastic nevi (HDN), are checked for cancer. HDN are present in 2‐10% of the white‐skinned population and may look like melanoma, a possibly deadly form of skin cancer. However, doctors disagree whether melanomas develop directly out of HDNs. As a result, some doctors advise removing more skin after a biopsy to make sure HDNs are completely removed. Recent research suggests that simple viewing of the HDN biopsy, might be a safe option instead of surgical removal. The aim of this study, from the University of North Carolina in the U.S.A., was to look at past studies for how often melanomas develop in patients who either had their HDNs surgically removed or simply viewed by experts. The authors found 12 studies with over 2, 600 HDN either observed or removed. The rate of melanoma development was low in both the observed (0.39%) and the removal (0.44%) groups. The authors concluded that most HDNs can be safely observed with low risk for melanoma development at the site of the HDN biopsy. However, the quality of the evidence reviewed was low, therefore more research is still needed to guide decision‐making by doctors. Abstract : Linked Article: Vuong et al. Br J Dermatol 2018;179 :590–598